Penerapan Blended Learning Dalam Upaya Meningkatkan Pemahaman Masyarakat Terhadap Konservasi Gajah Sumatera di Kabupaten Mila, Aceh - Hafnati Rahmatan; Abdullah Abdullah; Iswadi Iswadi; Ikhlas Wahid; Yuri Gagarin; Zulfikar Zulfikar (Postgraduate, University of Mataram, 2022)
The lack of knowledge and understanding of the people of Mila District on animal conservation causes conflicts between animals and the local community. One method that can be used to increase public understanding of the importance of maintaining elephant conservation is to apply the blended learning method. The purpose of this study was to determine the effectiveness of blended learning to increase public understanding of elephant conservation. This research was conducted in July 2022 in Mila sub-district, Pidie district. The research method used is an experimental method and the research design used is a questionnaire. Data was collected using a questionnaire in the experimental class and the control class with 25 respondents each. Analysis of the questionnaire data used a Likert scale by calculating the number of scores, then normality, and homogeneity tests were carried out to test the hypothesis using the independent t-test. The results of this study obtained the average score of the experimental class was 106.80 and the control class was 80.60. Questionnaire score data is data that is normally distributed with a value of (0.503>0.05) for the experimental class and (0.482>0.005) for the control class. Questionnaire score data is homogeneous data with a value (0.353> 0.05). The value of the hypothesis test is (0.000 <0.05). This study concludes that there are differences or improvements between blended learning and conventional methods